PENGARUH PENGGUNAAN GAME EDUKASI DENGAN BERBANTUAN WORDWALL TERHAADAP MOTIVASI BELAJAR SISWA KELAS III SDN 105339 BINJAI BAKUNG PADA PELAJARAN MATEMATIKA - Fitri; Safrida Napitupulu; Sukmawarti; Dinda Yarshal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is to determine the effect of using educational games with wordwall as an aid on students' learning motivation of grade III SDN 105339 Binjai Bakung in Mathematics lessons. This type of research is a quasi-experimental study with a quantitative approach. The design used is Nonequivalent Control Group Design. The participants of this study were all students of grade IIIA UPT SPF SDN 105339 Binjai Bakung, Pantai Labu District, Deli Serdang Regency, totaling 28 students. The population in this study were all students of grade III UPT SPF SDN 105339 Binjai Bakung. The sample used in this research was a Probability Sampling technique. The results of this study are that the effect of using educational games assisted by wordwall on the learning motivation of grade III students of SDN 105339 Binjai Bakung in Mathematics lessons, especially the material on presenting data in tables. it can be concluded that the results of the study show that there is a significant effect of using the Wordwall educational game on students' learning motivation. This is proven through the independent sample t-test statistical test which produces a significance value (Sig. 2-tailed) of 0.000, which is smaller than the significance level of 0.05. This means that there is a significant difference between the learning motivation of students who use Wordwall and students who do not use it. Students who use Wordwall show a higher increase in learning motivation. Learning with Wordwall creates a more interactive, fun, and challenging learning atmosphere, so that students are more active and motivated. Although there are several obstacles such as limited time and facilities, the use of Wordwall has proven effective in increasing students' learning motivation in Mathematics.